Patterns of engagement in leisure-time physical activities of workers with different economic status: a descriptive analysis - Kelly Samara da Silva; Adair da Silva Lopes; Giovâni Firpo Del Duca; Leandro Martin Totaro Garcia; Markus Vinicius Nahas (Universidade Federal de Santa Catarina, 2013)
People with different economic levels may have peculiar characteristics with respect to patterns of engagement in leisure-time physical activity (LTPA). This information is crucial to improving public policies. The objective of this study was to describe the patterns of engagement (type, companionship, and setting) in LTPA by gender, according to income strata in workers. Cross-sectional study conducted from 2006 to 2008 in 23 of the 26 Brazilian states and the Federal District (n=46,981). The sample consisted of workers who reported engaging in LTPA (n=25,479). A standardized self-completion questionnaire was applied. The following variables were investigated: type of LTPA - sports, walking, cycling/running, fitness, and others; companionship for LTPA - alone, with a partner, or in a group; and setting - clubs/gyms, streets/parks, and others, according to monthly family income (low, middle and high). We analyzed frequency distribution and applied a 95% confidence interval. Prevalence and 95% confidence intervals were calculated. Sports was the activity most engaged in by low- (50.2%) and middle-income (42.3%) workers, while walking predominated in high-income individuals (31.0%). LTPA in groups was greater in low- (52.0%) and middle-income (50.4%) workers, and lower intheir high-income counterparts (38%). Low- (47.0%) and middle-income (41.2%)workers used streets/parks more frequently, whereas high-income workers reported primarily using clubs/gyms (40.4%). It was concluded that low- and middle-income workers reported engaging in sports, in LTPA in groups, and using mainly public settings, while those with high-incomes engaged more in walking, in LTPA in groups or alone, and used more private settings.